1984
DOI: 10.2170/jjphysiol.34.485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of external calcium reduction on biphasic potassium contractures and action of divalent cations on the calcium reduction in frog single twitch muscle fibers.

Abstract: The effects of external Ca2+ reduction on the biphasic potassium (K) contractures and the action of divalent cations under conditions of the Ca2+ reduction were examined in detail, using frog single twitch muscle fibers. The peak tension of the initial component of 80 mM K+ contractures was greatly potentiated by exposing the fiber to low Ca2+ solution for 30 sec, and the degree of this potentiation was decreased with increasing the exposing time. In contrast, the peak tension of the secondary component was ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

1984
1984
1988
1988

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…6b). This effect of reduction in concentration of external Ca2+ is similar to that reported in our previous paper (TsUTSU-URA et al, 1984b). These changes were not observed in a solution containing Mn2+ (Fig, lc, d).…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…6b). This effect of reduction in concentration of external Ca2+ is similar to that reported in our previous paper (TsUTSU-URA et al, 1984b). These changes were not observed in a solution containing Mn2+ (Fig, lc, d).…”
Section: Methodssupporting
confidence: 92%
“…The preparation of single fibers from semitendinosus muscle of the frog (Rana japonica), the method of measurement of mechanical responses, the preparation of the solutions, and chemicals used were described previously (NAGAI et al, 1979;TAKAUJI et al, 1980TAKAUJI et al, , 1982bTsUTSU-URA et al, 1984b). Figure 1 shows the effect of Mn2 + on biphasic K contractures of a single twitch muscle fiber of a frog in a low Ca2+ solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 -iv in OBA and HOTTA, 1984). Since the work of FRANK (1962) appeared, it has been known that several divalent cations, including Co2+ and Nit +, could substitute for extracellular Ca2+ in the maintenance of potassium contracture with different degrees of effectiveness, in frog muscles (LoRKovIC, 1967;CAPUTO, 1981;LoRKovIc and RUDEL, 1983;TsUTSU-URA et al, 1984). Thus, we assessed the relative effectiveness of divalent cations on the maximum tension induced by 5µM Ag+.…”
Section: Effects Of Divalent Cations and Ttx On Ag+-induced Contractionsmentioning
confidence: 99%
“…l-9), therefore, it can be concluded that the inhibitory and potentiating changes of peak tension produced in parallel with the shortening of the time course of K contractures, which were induced by prolonged conditioning depolarization and during repriming or by reduction in external Ca2+ concentration, are generally determined by a balance between the activation and the inactivation processes of the secondary component. In our series of works concerning the biphasic K contractures (TAKAUJI et al, 1980(TAKAUJI et al, , 1982TsUTSU-URA et al, 1984), the question has been raised whether the contractile inactivation is involved in the initial component. The present result shown in Fig.…”
Section: Discussionmentioning
confidence: 99%